1993
DOI: 10.1093/nar/21.7.1677
|View full text |Cite
|
Sign up to set email alerts
|

E.colihost strains significantly affect the quality of small scale plasmid DNA preparations used for sequencing

Abstract: Several methods have been reported for the small scale preparation of plasmid DNA for sequencing (1-9), but little attention has been given to the effect of the E.coli host strain on the quality of the sequence obtained from double-stranded DNA. It has been observed that endonuclease A (endA4+) E. coli strains may produce nicked plasmid DNA resulting in 'shadow' bands on sequencing gels (1, 8), but no systematic evaluation of this phenomenon has been performed. We have found that of ten host strains tested, DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0
9

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(119 citation statements)
references
References 8 publications
2
108
0
9
Order By: Relevance
“…Strains-The E. coli strains used were DH5␣ (FЈ fhuA2 ⌬(argF-lacZ)U169 phoA glnV44 ⌽80 ⌬(lacZ)M15 gyrA96 recA1 relA1 endA1 thi-1 hsdR17a) (27) for cloning experiments and BL21(DE3) (F Ϫ r B Ϫ m B Ϫ gal ompT (int::P lacUV5 T7 gen1 imm21 nin5) (28) for expression and purification of enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…Strains-The E. coli strains used were DH5␣ (FЈ fhuA2 ⌬(argF-lacZ)U169 phoA glnV44 ⌽80 ⌬(lacZ)M15 gyrA96 recA1 relA1 endA1 thi-1 hsdR17a) (27) for cloning experiments and BL21(DE3) (F Ϫ r B Ϫ m B Ϫ gal ompT (int::P lacUV5 T7 gen1 imm21 nin5) (28) for expression and purification of enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial Strains and Growth Conditions-E. coli JM109 or DH5␣ (11,12) was used as a carrier for the plasmids described. All plasmids used in this study are listed in supplemental Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…17 This enzyme is not essential and its biological role in E. coli is still unknown as mutants resemble wild-type cells in terms of growth rate, phage propagation and conjugation properties. 18 Various studies 19,20 have found that EndA − strains produce DNA of higher quality than EndA + E. coli strains. A DNA fragment containing endA 21 was used to construct an M13 Km R suicide vector.…”
Section: Correspondence: J Crouzetmentioning
confidence: 99%